2018
DOI: 10.1017/s0007114518002143
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnosis plasma concentrations of enterolactone and survival after colorectal cancer: the Danish Diet, Cancer and Health cohort

Abstract: The association between lifestyle and survival after colorectal cancer has received limited attention. The female sex hormone, oestrogen, has been associated with lower colorectal cancer risk and mortality after colorectal cancer. Phyto-oestrogens are plant compounds with structure similar to oestrogen, and the main sources in Western populations are plant lignans. We investigated the association between the main lignan metabolite, enterolactone and survival after colorectal cancer among participants in the Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Concentrations of the super elongation complex component, ENL, were associated with colorectal cancer‐specific mortality. 222 Recent studies have shown that the condensates formed by ENL can isolate and concentrate positive TF b in inactive HEXIM1 and activate transcription processes. 83 BRD4 is strongly enriched at TERT promoter in colon cancer cells.…”
Section: Biomolecular Condensates Serve As Therapeutic Targets For Di...mentioning
confidence: 99%
See 1 more Smart Citation
“…Concentrations of the super elongation complex component, ENL, were associated with colorectal cancer‐specific mortality. 222 Recent studies have shown that the condensates formed by ENL can isolate and concentrate positive TF b in inactive HEXIM1 and activate transcription processes. 83 BRD4 is strongly enriched at TERT promoter in colon cancer cells.…”
Section: Biomolecular Condensates Serve As Therapeutic Targets For Di...mentioning
confidence: 99%
“…Colorectal cancer originates in the mucosal epithelium of the colon and rectum. Concentrations of the super elongation complex component, ENL, were associated with colorectal cancer‐specific mortality 222 . Recent studies have shown that the condensates formed by ENL can isolate and concentrate positive TF b in inactive HEXIM1 and activate transcription processes 83 .…”
Section: Biomolecular Condensates Serve As Therapeutic Targets For Di...mentioning
confidence: 99%
“…The outcome of the study was incidence of CRC, differentiated into colon cancer (CC) and rectum cancer (RC), identified through the Danish Cancer Registry and defined on the basis of relevant diagnostic codes from International Classification of Diseases 10 codes C18 (CC), C19 (cancer in the rectosigmoid junction), and C20 (RC)). Cancers coded as C19 were grouped with all CCs (C18), and cancers of the rectum (C20) were grouped as RC [24][25][26]. Participants were followed for incidence of CRC from inclusion in DCH and up to 31 December 2016.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…For example, we published recently our first Special Themed Issue on 'Nutrition and Cancer' which contains twelve peer-reviewed articles (see https://www.cambridge.org/core/journals/british-journalof-nutrition/issue/781E01A32EEB80B9745F37F868830915). This Issue is accompanied by a specially commissioned animation, based on the paper by Kyrø et al (6) , which was designed to communicate the findings from the study to non-specialist audiences though social media as well as via the BJN website. Our second Special Themed Issue on 'Cut-Offs for Nutritional Status in Nutrition Research' will be published shortly.…”
Section: Towards the Futurementioning
confidence: 99%